A covariance structure analysis of flicker sensitivity - Mayer, Melanie J.; Dougherty, Robert F.; Hu, Li-Tze (Vision research (Oxford), 1995)
We tested whether linear structural models of the mechanisms underlying flicker sensitivity could reproduce the variance-covariance matrix of temporal contrast sensitivity data. Monocular sensitivities to frequencies between 2.5 and 45 Hz were measured for 124 subjects, ages 18–88 yr. Exploratory factor analyses revealed that both a two-mechanism and a three-mechanism model could adequately account for the data. Furthermore, confirmatory factor analyses and full structural equation models, using age as an explanatory variable, supported both models, with the three-factor model giving a somewhat better representation of the data. Parsimony favors the two-mechanism model. But patterns of loss associated with pre-exudative age-related maculopathy are more easily understood in terms of three underlying mechanisms.